2015
DOI: 10.1186/s12937-016-0130-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of an undenatured type II collagen supplement in modulating knee osteoarthritis symptoms: a multicenter randomized, double-blind, placebo-controlled study

Abstract: BackgroundUndenatured type II collagen (UC-II) is a nutritional supplement derived from chicken sternum cartilage. The purpose of this study was to evaluate the efficacy and tolerability of UC-II for knee osteoarthritis (OA) pain and associated symptoms compared to placebo and to glucosamine hydrochloride plus chondroitin sulfate (GC).MethodsOne hundred ninety one volunteers were randomized into three groups receiving a daily dose of UC-II (40 mg), GC (1500 mg G & 1200 mg C), or placebo for a 180-day period. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
116
2
22

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(146 citation statements)
references
References 33 publications
(35 reference statements)
6
116
2
22
Order By: Relevance
“…After the removal of duplicates, a total of 7080 studies was identified in the search. Following full‐text screening, 71 studies were identified for inclusion, with 23 eligible for meta‐analysis. The abstracts for the majority of the papers were not sufficiently detailed to determine whether the full text should be retrieved.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After the removal of duplicates, a total of 7080 studies was identified in the search. Following full‐text screening, 71 studies were identified for inclusion, with 23 eligible for meta‐analysis. The abstracts for the majority of the papers were not sufficiently detailed to determine whether the full text should be retrieved.…”
Section: Resultsmentioning
confidence: 99%
“…Approximately 30% ( n = 21) of the studies were conducted in the USA , with five undertaken in Australia , four conducted in each of Germany , Japan and Spain , and three conducted in each of Denmark , Finland , Sweden , Iran and the Netherlands . Of the included studies, 47 were randomised controlled trials (RCT) , eight were nonrandomised trials , nine were pre–post studies , six were randomised cross‐over trials and one a longitudinal study .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of reports further substantiate this idea, demonstrating that various preparations of orally administered type 2 collagen effectively ameliorate collagen-induced arthritis in mice [51], in obese arthritic dogs [36], and in equine OA [52]. Remarkably, they have also been shown to have therapeutic efficacy in managing symptoms in human OA [53]. Similarly, oral supplementation with a type 1 collagen hydrolysate has been shown to structurally improve the thickness of articular cartilage in OA via gadolinium-enhanced MRI [54], suggesting potential disease-modifying capability of this agent.…”
Section: Discussionmentioning
confidence: 99%
“…Data in the literature show that the treatment of OA patients with UC-II increases the mobility and the functionality of the joints and reduces pain [49,50,51,52]. In an animal model, UC-II influences the humoral and cellular immune response through the T-regulatory cell secreting cytokines such as IL-10 and transforming growth factor-β which inhibit the immune response to collagen type II present in the extracellular matrix of the articular cartilage [53,54].…”
Section: Nutraceuticalsmentioning
confidence: 99%